(untitled) (Research, Society and Development, 2023)
Objective: Analyze the prevalence of mandibular accessory foramina and canals using cone-beam computed tomography (CBCT). Methodology: 136 mandibles divided into 10 predetermined areas were analyzed through CBCT looking for accessory foramina and canals. The Chi-square and Wilcoxon tests were used. Results: We found 1.316 accessory foramina, which 486 were accompanied by canals. 70.3% of accessory foramina were on the internal mandibular surface, most below the mylohyoid line and genial tubercles. The M1 area had the highest number of foramina, especially in the internal surface. The right mandibular side revealed a significantly greater number of foramina when compared to the left side. The mean diameter of accessory foramina analyzed was 0.85mm. Most of the accessory canals were on the internal mandibular surface, with a longer average length when compared to external surface canals. Conclusion: Our study showed that more detailed studies of accessory mandibular foramina and canals should be carried out, since a high prevalence of these structures and they have not named or classified yet. Furthermore, procedures that reach the internal mandibular surface, especially the anterior region, may be more subject to complications, as well as failure of anesthetic blocks on the right side of the mandible.